2009
DOI: 10.1158/0008-5472.sabcs-09-2028
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Paclitaxel by ChemoFx assay Correlates with Estrogen Receptor Status and Changes in Apoptosis Pathway in Human Breast Cancers.

Abstract: Background: Paclitaxel belongs to the taxane family of therapeutics, which have emerged as critically important drugs for breast cancer treatment. In addition to inhibiting cell growth by interfering with microtubule disassembly, its mechanism of action also includes induction of apoptosis. Recent studies suggest that besides being a key predictor for endocrine therapy response, Estrogen Receptor (ER) status also influences sensitivity of breast cancer to paclitaxel, with ER negative tumors being more responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The PI model characterizes the net rates of growth and invasion of the glioma cells contributing to this overall profile, a sum of individual cell behaviors. Swanson et al have demonstrated that D and ρ can be calculated on a patient-specific basis and can vary widely, even for patients within the same histological grade (Harpold et al, 2007; Swanson et al, 2008a; Szeto et al, 2009b; Wang et al, 2009; Rockne et al, 2010). (B) A simulation of the reaction-diffusion mathematical model on an anatomically accurate brain phantom (Cocosco et al, 2004) with differential motility in gray and white matter as proposed by Swanson (1999).…”
Section: The Clinical Challenge Of Patient-specific Prognosis and Trementioning
confidence: 99%
See 4 more Smart Citations
“…The PI model characterizes the net rates of growth and invasion of the glioma cells contributing to this overall profile, a sum of individual cell behaviors. Swanson et al have demonstrated that D and ρ can be calculated on a patient-specific basis and can vary widely, even for patients within the same histological grade (Harpold et al, 2007; Swanson et al, 2008a; Szeto et al, 2009b; Wang et al, 2009; Rockne et al, 2010). (B) A simulation of the reaction-diffusion mathematical model on an anatomically accurate brain phantom (Cocosco et al, 2004) with differential motility in gray and white matter as proposed by Swanson (1999).…”
Section: The Clinical Challenge Of Patient-specific Prognosis and Trementioning
confidence: 99%
“…The MRI-detectable edge of the lesion is superimposed as a dark gray contour emphasizing the extent of invasion well beyond the threshold of detection. From Wang et al (2009) with permission from Cancer Research.…”
Section: The Clinical Challenge Of Patient-specific Prognosis and Trementioning
confidence: 99%
See 3 more Smart Citations